Prevention of online gambling crimes to maintain social structure stability - Anggoro, Tri Cahyono; Santoso, Bambang (Privietlab, 2025)
The advancement of digital technology has led to the proliferation of online gambling practices in Indonesia, significantly affecting the stability of social structures. This study aims to examine the relationship between online gambling crimes and social disintegration, with a particular focus on their impact on families, communities, and cultural value. Employing a normative legal research method with statutory, conceptual, and comparative approaches, this study analyzes existing regulations, including those stipulated in the Criminal Code (KUHP) and the Electronic Information and Transactions Law (UU ITE), as well as legal concepts related to cybercrime prevention. The research findings indicate that online gambling triggers financial problems, family breakdowns, increased criminality, moral degradation, and weakened social cohesion, all of which negatively affect the social structure of communities. Preventive efforts require a holistic strategy, including strict law enforcement, the use of advanced detection technologies, website blocking, restrictions on virtual private network (VPN) access, digital literacy education, active involvement of educational and religious institutions, formation of anti-gambling communities, rehabilitation support for addicts, and economic empowerment of vulnerable groups. International collaboration through information-sharing and extradition mechanisms is crucial for addressing cross-border offenders. This study underscores the importance of cross-sectoral synergy and a multidisciplinary approach to prevent the widespread destructive impact of online gambling on social structures.